Aeroacoustics response of wind turbine blade profiles in normal and icing conditions. Issue 3 (June 2018) - Caicedo, Edison H; Virk, Muhammad S
This article describes a multiphase computational fluid dynamics–based numerical study of the aeroacoustics response of symmetric and asymmetric wind turbine blade profiles in both normal and icing conditions. Three different turbulence models (Reynolds-averaged Navier–Stokes, detached eddy simulation, and large eddy simulation) have been used to make a comparison of numerical results with the experimental data, where a good agreement is found between numerical and experimental results. Detached eddy simulation turbulence model is found suitable for this study. Later, an extended computational fluid dynamics–based aeroacoustics parametric study is carried out for both normal (clean) and iced airfoils, where the results indicate a significant change in sound levels for iced profiles as compared to clean.